Prevalence of refractive errors in the Slovak population calculated using the Gullstrand schematic eye model - Popov, Ivajlo; Valášková, Jela; Štefaničková, Jana; Krásnik, Vladimír; Tomčíková, Dana (Czech and Slovak Ophthalmology, 2017)
Purpose: Large part of the population suffers of some kind of refractive errors. It is supposed that their prevalence could change with the development of the society. The aim of this study is to determine the prevalence of refractive errors using calculations based on the Gullstrand schematic eye. Methods: We used Gullstrand schematic eye to calculate refraction retrospectively. Refraction was presented as needed glasses correction in vertex distance 12 mm. Necessary data was obtained with the optical biometer Lenstar LS900. Data which could not be obtained due to the device limitation were substituted by theoretical data from the Gullstrand schematic eye. Only analyses from the right eyes were presented. Data were interpreted using descriptive statistics, Pearson correlation and t-test. Statistical tests were conducted at significance level of 5 %. Results: In our sample were 1663 patients (665 males, 998 females) in age from 19 to 96 years. Average age was 70,8 ± 9,53 years. Average refraction of the eye was 2,73 ± 2,13D (males 2,49 ± 2,34, females 2,90 ± 2,76). Mean absolute error from emmetropia was 3,01 ± 1,58 (males 2,83 ± 2,95, female 3,25 ± 3,35). 89,06 % of the sample was hyperopic, 6,61 % was myopic and 4,33 % emmetropic. We did not find correlation between refraction and the age. Conclusion: Females were more hyperopic than males. We did not find any statistically significant hypermetopic shift of the refraction with the age. According to our estimation the calculations of refractive errors showed hypermetropic shift of more than +2D from reality. Our results could be used in future for comparing prevalence of refractive errors using same methods as we used.
Keywords: emetropie; Refractive Errors; senioři nad 80 let; refrakční vady; Humans; Prevalence; Data Interpretation, Statistical; Biometry; lidé středního věku; Middle Aged; Aged, 80 and over; Models, Biological; Slovakia; mladý dospělý; refraktometrie; Slovenská republika; mužské pohlaví; biologické modely; refrakce oka; Refraction, Ocular; Statistics as Topic; ženské pohlaví; Gullstrand schematic eye; statistika jako téma; Refractometry; interpretace statistických dat; biometrie; lidé; prevalence; Gullstrandův model oka; Emmetropia; Aged; senioři; Young Adult; Male; Female